Tracheal epithelial-myoepithelial carcinoma associated with sarcoid-like reaction: A case report. (2015) - Dong, Huawei; Tatsuno, Brent K.; Betancourt, Jaime; Oh, Scott S.
Abstract: Epithelial-myoepithelial carcinomas are rare tumors that primarily originate in the salivary glands but have also been found in the tracheobronchial tree. We report the first case of epithelial-myoepithelial carcinoma associated with sarcoidosis. A 61 year old Hispanic man presented with altered mental status and hypercalcemia. Imaging revealed diffuse intra-thoracic and intra-abdominal lymphadenopathy. A diagnostic bronchoscopy was performed where an incidental tracheal nodule was discovered and biopsied. Pathology was consistent with epithelial-myoepithelial carcinoma. Lymph node biopsy demonstrated non-caseating granulomas consistent with sarcoidosis. Patient underwent tracheal resection of the primary tumor with primary tracheal reconstruction. Hypercalcemia subsequently normalized with clinical improvement. Repeat CT imaging demonstrated complete resolution of lymphadenopathy. Our findings are suggestive of a possible paraneoplastic sarcoid-like reaction to the epithelial-myoepithelial carcinoma with associated lymphadenopathy and symptomatic hypercalcemia.